Malay loanwords in English: Reasons for its survival, disappearance and revival / Nazima Versay Kudus - Versay Kudus, Nazima (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2007)
Word borrowing is a result of cultural contact between two language communities. With the advent of science and technology, it is inevitable that the Malay language have to borrow words from the English lexicon. The reverse, though, not so aggressively takes place. Most Malay Loanwords in English are socially motivated borrowing or in other words, cultural words pertaining to day-to-day life of the people concerned. The purpose of this paper is to examine the nature of the survived words (both with similar meanings and those that change), disappeared words and to suggest avenues to popularise Malay loanwords in English.